2015
DOI: 10.1177/1687814014568500
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface roughness on the friction property of textured surface

Abstract: In contrast with dimple textures, surface roughness is a texture at the micro-scale, essentially which will influence the load-bearing capacity of lubricant film. The numerical simulation was carried out to investigate the influence of surface roughness on friction property of textured surface. The lubricant film pressure was obtained using the method of computational fluid dynamics according to geometric model of round dimple, and the renormalization-group k-e turbulent model was adopted in the computation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The results showed that both the surface texture and surface roughness play important roles, and friction reduction effect of the textured surface varies under different surface roughness. Zhou et al 6 investigated the influence of the surface roughness on friction property of the textured surface using the method of the computational fluid dynamics. Their results suggested that the load-carrying capacity is closely related to surface texture, surface roughness, and the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both the surface texture and surface roughness play important roles, and friction reduction effect of the textured surface varies under different surface roughness. Zhou et al 6 investigated the influence of the surface roughness on friction property of the textured surface using the method of the computational fluid dynamics. Their results suggested that the load-carrying capacity is closely related to surface texture, surface roughness, and the interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…This means that a well-controlled tangential displacement and less drift are obtained. The literature shows that textured surfaces can reduce friction [67,68], and, as a result, the tangential displacement will also be reduced. Experiments in which the drift is measured at textured surfaces should be performed.…”
Section: Recommendationsmentioning
confidence: 99%
“…Kadleckova and co-workers [2] reported that with the multistep etching process, the aluminumalloy substrate can be effectively modified and textured to the same morphology, regardless of the initial surface roughness. In [3] the authors investigated the effects of surface roughness on the tribological properties of a textured surface. Their investigations show that in contrast with dimple textures, surface roughness is a texture at the micro-level, which will essentially influence the load-bearing capacity of lubricant film.…”
Section: Introductionmentioning
confidence: 99%